Process parameter influence on performance of friction taper stud welds in AISI 4140 steel - Hattingh, D.G.; Bulbring, D.L.H.; Els-Botes, A.; James, M.N. (Materials in engineering, 2011)
► In this study we extend the FTSW technique to higher strength AISI 4140 steel. ► The study quantifies the influences on weld integrity of process parameters. ► Weld cycle time reduces as the forging force increases. ► Maximum tensile strength was achieved with a (HLH) combination of process parameters. ► Most dominant defect is the flash crack which can lead to lower tensile strengths. Friction taper stud welding is a new variant of friction welding which has been developed from the principles of friction hydro-pillar processing. This paper considers the effect of weld process parameters on weld defects, macrostructure and mechanical properties in AISI 4140 steel. It also presents 3D residual stress data for a typical friction taper stud weld. Applied downwards force, rotational speed and plunge depth (equivalent to consumable length) of the stud tool were systematically varied whilst measuring tool torque and temperature at several locations during welding. A simple Taguchi analysis was then used to relate process parameters and weld tensile strength. The combinations of parameters leading to high tensile strength are identified and linked to the occurrence of specific weld defects.